Football Traumatology New Trends - Volpi, Piero (Springer International Publishing : Imprint: Springer, 2015)
This book provides a comprehensive guide to the evaluation, treatment, and rehabilitation of musculoskeletal injuries commonly experienced by football (soccer) players. It will be of particular value for orthopedists and sports medicine practitioners, and will provide the information required by trainers and medical staff regarding the traumatic lesions associated with the sport. It is also anticipated that the book will assist in reducing the risk of trauma in footballers. The new edition has been revised to reflect advances in knowledge and practice and will be more valuable than ever, given that the risk of trauma continues to increase owing to the intensity and speed of modern football, the current training methods, and technical and tactical innovations. Injuries are a major adverse event during a footballer's career, and they require appropriate medical and/or surgical treatment and rehabilitation. The overviews provided in this book will help in delivering such care.